Does general anesthesia have a clinical impact on intraocular pressure in children?. Issue 9 (5th July 2016) - Termühlen, Julia; Gottschalk, Antje; Eter, Nicole; Hoffmann, Esther M.; Van Aken, Hugo; Grenzebach, Ulrike; Prokosch, Verena
Summary: Background: Reliable measurement of intraocular pressure (IOP) is crucial in pediatric patients with suspected glaucoma. General anesthesia (GA) is usually needed in infants to allow a thorough examination. However, anesthesia itself may influence IOP, depending on the type used and the depth of sedation. The purpose of this study was to evaluate the normal distribution of IOP during GA in healthy children and to analyze differences in IOP relative to the anesthetics used and the measurement time point. Methods: Approval for this observational study was received from the local institutional review boards and written informed consent was obtained from the children's parents. A total of 100 pediatric patients with no history of glaucoma scheduled for nonintraocular surgery underwent general anesthesia, induced with sevoflurane (s) or propofol (p) and maintained with either sevoflurane with remifentanil (S) or propofol with remifentanil (P). The patients were grouped to one of four subgroups (sS, sP, pP, pS) depending on the anesthetics used during induction and maintenance. Hemodynamic parameters and IOP were measured in both eyes at four defined time points: before anesthesia induction (M1); in apnea immediately after induction and before insertion of a laryngeal mask airway (M2); in deep anesthesia during mechanical ventilation (M3); and after extubation (M4), using a handheld Perkins applanation tonometer. Differences in IOP in both eyes during the measurement periods were analyzed using multivariate repeated‐measures analysis of variance and Tukey‐HSD as a posthoc test with statistical significance set at P < 0.05. Pearson correlation coefficient was used to investigate further relationships between heart rate, systolic blood pressure, and IOP. Results: General anesthesia reduced IOP significantly. The mean IOP was normally distributed, with a mean of 7.4 ± 2.89 mmHg at M1. It decreased significantly to a minimum of 5.6 ± 3.04 mmHg ( P < 0.01) at M2 and increased significantly to 7.2 ± 2.51 mmHg ( P < 0.01) at M3 and again to 8.4 ± 3.72 mmHg ( P = 0.03) at M4. All four subgroups (sS, sP, pP, pS) showed comparable decreases in IOP between M1 and M2. During deep anesthesia (M3) and during reversal (M4), the IOP increased again in all groups. During reversal (M4), however, the sS group had a significantly lower IOP than the pP group ( P = 0.001) and sP group ( P = 0.02). There were no correlations between changes in IOP and gender, age, or type of surgery. Conclusions: Sevoflurane and propofol, both in combination with remifentanil, significantly lower IOP in children. Individual IOP levels rise and fall during anesthesia, depending on the time point of measurement. The lowest IOP can be measured immediately after induction of anesthesia. This needs to be taken into account when measuring IOP in children. Abstract :